PENGEMBANGAN MODEL KURIKULUM TERPADU: TUJUAN, ISI, IMPLEMENTASI DAN HASIL - Muslem Muslem (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to construct an integrated curriculum model, encompassing its objectives, content, implementation, and outcomes. Selecting an integrated curriculum model as a theme is a response to the issue of curriculum dichotomy (knowledge), although it does not completely resolve the issue. This study employed a qualitative library research approach, focusing on collecting and analyzing data from various relevant literature sources. Data were obtained from scientific books, academic journals, research articles, curriculum documents, and trusted digital sources discussing the integrated curriculum. The results indicate that developing a curriculum model begins with the formulation of objectives, content, implementation, and outcomes or evaluation. Then, modifications are made to each component of the curriculum to construct an integrated curriculum model. Although this does not resolve the issue of curriculum dichotomy in educational institutions, the space for scientific dialectics is very open and possible with the existence of an integrated curriculum model with Islamic values, which then provides new perspectives for students.